A reinvigorated strategy for the analysis of optimal parameters for modeling of Solar Photovoltaic modules under variable conditions. (November 2021) - Raj, Sonali; Kumar, Ramesh
Abstract: In today's world, Solar Photovoltaic energy sources have accredited robustness and reliability in the context of generation, transmission, and distribution of power for the end-users and utility customers. The accurate parameters analysis of Solar PV modules is necessary for the proper assessment, simulation, and optimization of power from Solar PV systems. The main goal of this paper is to apply a suitable approach to identify unspecified parameters of the PV module and at the same time to minimize (%) relative error and computation time to get better-optimized parameters for modeling of PV module. This paper presents a hybrid of a mathematical and iterative approach to analyze the appropriate parameters of the Solar PV model. Here, Root finding algorithms have been applied to extract the optimal unknown parameters of the PV modules by MATLAB programming. These algorithms are demonstrated on three distinct types of PV modules (Thin film, Monocrystalline, and Multicrystalline type) at standard test conditions and nominal operating conditions. These algorithms provide high precision and consume minimal time with ease of implementation. Extraction of parameters and simulation of the model is performed for validation based on datasheets of distinct types of PV modules using MATLAB/ SIMULINK software. The extracted precise parameters give rise to output characteristics of PV modules under variable environmental and electrical conditions. Relative error analysis has been evaluated to distinguish between different techniques applied for parameter extraction of PV modules. The relative error (%) of the proposed techniques for parameters extraction of PV modules varies from −0.5% to ＋0.5%, which shows the supercilious characteristic of the proposed techniques. Future exploration headings concerning the optimization of power from the Solar PV system are suggested.